2012
DOI: 10.1111/j.1744-7909.2012.01101.x
|View full text |Cite
|
Sign up to set email alerts
|

ROP11 GTPase Negatively Regulates ABA Signaling by Protecting ABI1 Phosphatase Activity from Inhibition by the ABA Receptor RCAR1/PYL9 in Arabidopsis

Abstract: The phytohormone abscisic acid (ABA) regulates many key processes in plants, such as seed germination, seedling growth, and abiotic stress tolerance. In recent years, a minimal set of core components of a major ABA signaling pathway has been discovered. These components include a RCAR/PYR/PYL family of ABA receptors, a group of PP2C phosphatases, and three SnRK2 kinases. However, how the interactions between the receptors and their targets are regulated by other proteins remains largely unknown. In a companion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 31 publications
3
54
1
Order By: Relevance
“…Note. When this paper was under preparation, another group reported that ROP11 interacted with ABI1 and regulated ABA responses (34,35), although authors found that ABI1 interaction with ROP11 occurs when the regulatory domain of ABI1 is deleted (35). It seems likely that different cross-talk nodes are present in subcellular compartments, such as the nucleus and cytosol, where they link alternate signals to ABA.…”
Section: Methodsmentioning
confidence: 99%
“…Note. When this paper was under preparation, another group reported that ROP11 interacted with ABI1 and regulated ABA responses (34,35), although authors found that ABI1 interaction with ROP11 occurs when the regulatory domain of ABI1 is deleted (35). It seems likely that different cross-talk nodes are present in subcellular compartments, such as the nucleus and cytosol, where they link alternate signals to ABA.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the activation of AtRop2 and AtRop6 by auxin has been reported to regulate the subcellular distribution of auxin transporters PIN1 and PIN2, which control PIN-mediated pattern formation and morphogenesis in leaves and roots (18 -20). AtRop10 and AtRop11 are specific negative regulators of abscisic acid responses (21,22). In addition, AtRop9 functions as a signal integrator of auxin and abscisic acid signaling and plays an important role in embryo development and lateral root formation in A. thaliana (23).…”
mentioning
confidence: 99%
“…The SNF1-RELATED PROTEIN KINASE TYPE 2 -phosphatase activity of ABSCISIC ACID-INSENSITIVE 2 is enhanced in the presence of the GTP-bound AtROP11 protein [21]. This interaction prevents the binding of the ABSCISIC ACID-INSENSITIVE 2 protein to its inhibitors: the abscisic acid receptor PYRABACTIN/PYRABACTIN-LIKE PROTEINs [55]. Therefore, the active AtROP11…”
Section: The Snf1-related Protein Kinase Type 2 Kinase Is Indirectly mentioning
confidence: 99%